Indole Propionic Acid (IPA), A Gut Microbiota-Derived Metabolite, in Active Pulmonary Tuberculosis (TB) Infection: A Case Control Study: A Case Control Study - Maulina, Novi; Hayati, Zinatul; Hasballah, Kartini; Zulkarnain, Zulkarnain (Trends in Sciences, 2024)
Introduction: A metabolomics study revealed that the tryptophan (Trp) pathway is upregulated in tuberculosis (TB) infection. Indole propionic acid (IPA) is a gut microbiota-derived tryptophan metabolite with antimycobacterial properties through TrpE inhibition and as ligand for AhR in in vitro and in vivo studies. TB infection is associated with gut dysbiosis. However, plasma IPA levels and related factors in active TB patients have not yet been explored. This study aimed to determine the differences and correlations between plasma IPA levels and patient characteristics (age, gender, BMI and GeneXpert result), IPA-producing gut microbiota (Clostridium sporogenes, Lactobacillus sp., and Peptostreptococcus anaerobius), and IFN-γ concentrations in active TB patients and healthy subjects. Materials and methods: A case-control study was performed in 29 active TB patients and 30 healthy controls (HCs) in Aceh, Indonesia. The plasma IPA and IFN-γ levels were measured by ELISA, and the relative abundance of gut microbiota was determined by quantitative PCR (qPCR). The results and discussion: Increased plasma IPA levels (median (IQR) of 22.2 pmol/L (21.3 - 23.9) vs. 18.9 pmol/L (17 - 22.8), p 0.000) were associated with active TB according to the adjusted model (AOR 1.36 (95 % CI 0.37 - 5.1)). Increase of plasma IPA level in higher mycobacterial load patients was found. Higher plasma IPA was positively associated with female, normo- and overweight status, and higher relative abundance of C. sporogenes. The metabolite could be used to discriminate active TB disease at a cutoff of 21.40 pmol/L (72 % sensitivity, 70 % specificity and AUC 0.77). Dysbiosis in IPA-producing bacteria was showed in active TB patients. Conclusion: Plasma IPA could be considered as TB biomarker, and it may also influence disease progression. Future works are needed to validate plasma IPA as biomarker in LTBI and other respiratory infection, as well as its role as biomarker of treatment monitoring response. HIGHLIGHTS The upregulation of the tryptophan (Trp) pathway in tuberculosis infection. Indole propionic acid (IPA) is a Trp metabolite with antimycobacterial properties Higher plasma IPA levels were found in TB patients than in healthy subjects. Dysbiosis of several IPA-producing gut microbiota was revealed in this study. GRAPHICAL ABSTRACT